Patient and Oncology Nurse Preferences for the Treatment Options in Advanced Melanoma: A Discrete Choice Experiment - Liu, Frank Xiaoqing (Cancer Nurs, 2019)
BACKGROUND: Understanding the perceptions of patients and oncology nurses about the relative importance of benefits and risks associated with newer treatments of advanced melanoma can help to inform clinical decision-making. OBJECTIVES: The aims of this study were to quantify and compare the views of patients and oncology nurses regarding the importance of attributes of treatments of advanced melanoma. METHODS: A discrete choice experiment (DCE) was conducted in US-based oncology nurses and patients diagnosed with advanced melanoma. Patients and nurses were enlisted through online panels. In a series of scenarios, respondents had to choose between 2 hypothetical treatments, each with 7 attributes: mode of administration (MoA), dosing schedule (DS), median duration of therapy (DoT), objective response rate (ORR), progression-free survival (PFS), overall survival (OS), and grade 3 or 4 adverse events (AEs). Hierarchical Bayesian logistic regression models were used to estimate preference weights. RESULTS: A total of 200 patients with advanced melanoma and 150 oncology nurses participated. The relative importance estimates of attributes by patients and nurses, respectively, were as follows: OS, 33% and 28%; AEs, 29% and 26%; ORR, 25% and 27%; PFS, 12% and 15%; DS, 2% and 3%; DoT, 0% and 0%; and MoA, 0% and 0%. CONCLUSION: Both patients and oncology nurses valued OS, ORR, and AEs as the most important treatment attributes for advanced melanoma, followed by PFS, whereas DS, DoT, and MoA were given less value in their treatment decisions. IMPLICATIONS FOR PRACTICE: Oncology nurses and patients have similar views on important treatment considerations for advanced melanoma, which can help build trust in shared decision-making.